Razvoj programske opreme z uporabo jezika UML - Živkovič, Aleš (Uporabna informatika (Ljubljana), 2000)
In the paper language for documenting software development artifacts will be presented. First the structure, diagram elements and supplemental expressive possibilities as an extension mechanisms for basis techniques will be described. Unfortunately, well-formed standard doesn`t define steps, inputs and outputs for each step. There is no single process suitable for all the environments. Process needs to be tailored to environment specific and continously improved. Recommendations for forming an object-oriented software development process will also be presented.
Keywords: procesni model; programska oprema; računalniški programi; računalništvo; UML